Modification of WHO diagnostic criteria for gestational diabetes: implications for classification of hyperglycemia in pregnancy - Imoh, Lucius C.; Asorose, Solomon A.; Odo, Alfred I.; Aina, Daniel O.; Abu, Alexander O.; Ocheke, Amaka N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Low and medium income countries (LMICs) especially in sub-Saharan Africa face unique challenges in screening and diagnosing hyperglycaemia in pregnancy. The implications of applying the 2013 WHO modifications for assessing hyperglycaemia in pregnancy in low resource settings are not known. We evaluated the significance of these recent changes in classification of hyperglycaemia among pregnant Nigerian women. Methods: We reviewed the records of Oral glucose tolerance test conducted on 600 pregnant women at the Jos University Teaching Hospital (JUTH) between July 2012 and June 2016. The collected data were analyzed using Statistical Package for Social Sciences version 18 (SPSS Inc., Chicago, IL, USA). Test for association was done using Fisher’s exact test. P < 0.05 was set as the level of significance. Results: The results show that 15.9%, 20.2% and 15.7% of the women had GDM according to WHO (1999), IADPSG and WHO (2013) diagnostic criteria respectively while 4.8% of the women had DM in pregnancy by WHO 2013 criteria. Overall, 30.2% and 23.9% of women who were classified as GDM by WHO 1999 criteria and IADPSG criteria respectively were qualified to be classified as DM in pregnancy according to the WHO 2013 criteria. Conclusions: The recent Modifications by the WHO 2013 guideline for classifying hyperglycemia in pregnancy may create non-uniform interpretation of OGTT. The confusion in classifying hyperglycemia among pregnant women referred between health centres may become more pronounced. There is an urgent need for a streamlined globally acceptable approach to assessing and classifying hyperglycemia in pregnant women.